Addicted to Facebook: Examining the roles of personality characteristics, gratifications sought and Facebook exposure among youths - Omar, Bahiyah; Subramanian, K. (Global Science and Technology Forum, 2013)
This study draws upon the Uses and Gratifications (U&G) theory and past studies on Facebook to deduce factors (i.e: personality characteristics and gratifications sought) that contribute to Facebook addiction amongst university students. Results of factor analysis reveal four dimensions of gratifications (i.e: content, process, social and technology) and introduce self-presentation as the fifth dimension for gratifications sought. Meanwhile, personality characteristics are also factor analyzed and the results show five traits (i.e: shyness, loneliness, powerful others control, internal control and externakohi_87 control) of Facebook users. Using a survey data collected from 400 undergraduate students of one of the public universities in Malaysia, this study tests direct relationships between these factors and Facebook addiction, and the effect of Facebook usage as a mediator to the relationships. The results show insignificant effect of the mediator. This study discovers, on the other hand, significant direct relationships between the factors (except for internal control) and Facebook addiction. Most importantly, the study finds that three dimensions of gratifications sought (i.e: content, self-presentation and social) and two of the personality characteristics (i.e: shyness and loneliness) are significant predictors to Facebook addiction among youths.